Management of pleural effusion in six cats - Satish Kumar , K.; Sangeetha, Abboori; Mohanambal, K; K. Ujwala; T. Ramya Sai (Indian Journal of Veterinary Medicine, 2024)
Six domestic cats that were presented to VCC, CVSc, Rajendranagar, with a history and signs of respiratory distress, cough, insomnolence, and weakness were considered for the study. Clinical examination revealed abdominal breathing, dyspnea, and dehydration. On auscultation low intensity respiratory and heart sounds were heard. Chest X-ray indicated a ground-glass appearance in the cranial lung lobe area, and ultrasound revealed anechoic areas in the thorax. Effusion was suspected, leading to ultrasound-guided thoracocentesis which relieved respiratory distress. CT scan was performed in some cases. Comprehensive diagnostics confirmed chylothorax in four cases and pleural effusion in two. The chylothorax cats were managed with rutin for 4 weeks whereas the cats with pleural effusion were managed with the antibiotic amoxicillin-clavulanate for 7 days. The cats were also treated with furosemide for 1 week. Following treatment 5 cats showed recovery from day 6 with improvement in dyspnea and cough, but one cat that was also positive for FIP collapsed after two weeks.